Socio-economic empowerment of women in Nepal through microfinance services - Bhusal, Pratima; Rana, Bikash (Devkota Journal of Interdisciplinary Studies, 2025)
This research investigates the role of microfinance in empowering women economically and socially in rural Nepal. It aims to assess how access to microfinance services affects women’s income, savings, asset ownership, decision-making power, and social standing. The study follows a descriptive research design, using structured questionnaires to collect primary data from 387 women across various rural districts of Nepal. A simple random sampling technique was applied to ensure representativeness. Statistical analysis, including descriptive statistics, correlation, and regression analysis, was performed using SPSS to examine the relationship between microfinance services and women’s empowerment. The findings reveal that microfinance significantly contributes to economic empowerment, with a strong positive correlation between microfinance participation and economic outcomes such as income generation and financial control. Social empowerment also improved, though to a lesser extent. Regression analysis showed that microfinance explains 57% of the variation in economic empowerment and 39.7% in social empowerment. However, barriers like male dominance, limited financial literacy, and cultural norms still hinder full empowerment. The research contributes to the ongoing discourse on gender and financial inclusion by offering fresh empirical evidence from rural Nepal. While previous studies have highlighted microfinance’s economic benefits, this study uniquely integrates both economic and social dimensions of empowerment. The findings highlight not only the positive impact of microfinance on women’s financial independence but also reveal the persistent challenges, such as male dominance and limited financial literacy, that hinder full social empowerment. It provides valuable insights for policymakers, microfinance institutions, and development practitioners focused on inclusive financial development.